THE CO-INTEGRATION OF INDONESIAN CAPITAL MARKETS TO ASEAN CAPITAL MARKETS AFTER THE COVID-19 PANDEMIC - Hary Saputra Sundoro; Grace Putlia; Caroline Caroline (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Most investors diversify their funds not only in the differ stocks but also in the other capital markets. Thus, Indonesian investors are likely to diversify the funds in capital markets of ASEAN countries. Pandemic COVID-19 makes a possibility that capital markets in ASEAN region are not co-integrated. The purpose of this study is to know the co-integration of Indonesian capital markets to ASEAN capital markets after pandemic COVID-19. The study is quantitative analysis with VECM method and daily data. The period starts from 08 May 2023 to 22 March 2024. The results state that ASEAN capital markets are still co-integrated after pandemic COVID-19. IHSG responds negatively to KLSE, but IHSG responds positively to STI, SETI and PSEI either in the short term or in the long term. Then, the Indonesian investors are able to diversify their funds into ASEAN capital markets after pandemic COVID-19. For the next research, a longer data is needed in order to run VECM method better.